2011
DOI: 10.1111/j.1600-0765.2011.01406.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of thymoquinone in a rat periodontitis model: a morphometric and histopathological study

Abstract: The present study showed that the oral administration of thymoquinone diminishes alveolar bone resorption in a rat periodontitis model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 36 publications
3
40
0
2
Order By: Relevance
“…Another study has shown that the alveolar bone loss due to periodontitis was reduced by gastric feeding of TQ to rats. This was accompanied by reduction in osteoclast number and raised osteoblastic activity in TQ-treated rats [29]. In studies using rheumatoid arthritis model, TQ was reported to reduce the serum levels of IL-1 and TNF-α, [30].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that the alveolar bone loss due to periodontitis was reduced by gastric feeding of TQ to rats. This was accompanied by reduction in osteoclast number and raised osteoblastic activity in TQ-treated rats [29]. In studies using rheumatoid arthritis model, TQ was reported to reduce the serum levels of IL-1 and TNF-α, [30].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TQ suppressed the adjuvant induced arthritis and also decreased the periodontitis in rat periodontitis model [10,11]. However the effect of TQ on RANKL induced osteoclastogenesis has not been investigated.…”
Section: Introductionmentioning
confidence: 95%
“…10 Recently, antioxidant therapies have been widely researched by investigators 4,8,11 as a result of their effect on bone metabolism via inhibition of osteoclastic activity and promotion of osteoblastic activity. Propolis, a substance made by the honeybee, is an effective antioxidant, antimicrobial, and anti-inflammatory agent.…”
Section: Introductionmentioning
confidence: 99%